2017
DOI: 10.3892/mmr.2017.6344
|View full text |Cite
|
Sign up to set email alerts
|

Substance P accelerates wound healing in type 2 diabetic mice through endothelial progenitor cell mobilization and Yes-associated protein activation

Abstract: Wound healing is delayed in diabetes due to a number of factors, including impaired angiogenesis and poor dermal healing. The present study demonstrated that subcutaneous administration of substance P (SP) accelerates wound healing in db/db type 2 diabetic mice (db/db mice). SP injection (10 nM/kg, subcutaneously) enhanced angiogenesis, induced the mobilization of endothelial progenitor cells (EPCs) and increased the number of EPC-colony forming units (EPC-CFUs) in the bone marrow of db/db mice. Immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…One additional study suggested that primarily CGRP, and to a lesser extent SP, influenced epidermal thickness and proliferation of keratinocytes in innervated skin models [ 60 ]. Besides that, the literature is lack of studies regarding the effect of free SP on the motility and proliferation of keratinocytes in vitro models, on the other hand data supply several evidences on wound closure activity by increasing of cell motility and proliferation after topically treatments with SP on skin wound in vivo or ex vivo [ 5 , 6 , 12 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…One additional study suggested that primarily CGRP, and to a lesser extent SP, influenced epidermal thickness and proliferation of keratinocytes in innervated skin models [ 60 ]. Besides that, the literature is lack of studies regarding the effect of free SP on the motility and proliferation of keratinocytes in vitro models, on the other hand data supply several evidences on wound closure activity by increasing of cell motility and proliferation after topically treatments with SP on skin wound in vivo or ex vivo [ 5 , 6 , 12 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, SP has been found to be decreased in skin biopsies from both type 1 and type 2 diabetic patients (Lindberger et al, 1989) and SP mRNA and protein expression is diminished in a rabbit model of type 1 diabetes (Pradhan et al, 2009). Exogenous treatment of diabetic wounds with SP resulted in faster healing in both mice and rats (Leal et al, 2015;Park et al, 2016;Um et al, 2017;Zhu et al, 2016). In addition, topical administration of SP on excisional wounds in a db/db mouse model led to increased leukocyte infiltration compared to saline treatment at the early stages post-wounding, suggesting a role for SP involvement during early inflammation in wound healing (Scott et al, 2008).…”
Section: Substance P (Sp)mentioning
confidence: 99%
“…In endothelial cells, SP is an established vasodilating factor by inducing the production of nitric oxide, consequently enhancing endothelial permeability and leukocyte extravasation into the underlying tissues (Pernow, 1983). It has been recently reported to promote the mobilization of endothelial progenitor cells in the wounded tissue of a murine model of type 2 diabetes and increase the amount of Yes-associated protein expression in the dermis (Um et al, 2017). Furthermore, it acts as a potent chemoattractant for immune cells, promotes elevated expression of endothelial leukocyte adhesion molecule-1 on human microvascular endothelial cells and leukocyte function-associated antigen-1 (LFA-1) on murine endothelial cells and lymphocytes and can raise the levels of an array of Fig.…”
Section: Substance P (Sp)mentioning
confidence: 99%
“…Substance P also appears to play a role in angiogenesis, as in vivo studies examining impaired wound healing in diabetics found that subcutaneous injection of substance P into both normal mice [80] and type 2 diabetic model mice [81] accelerated wound closing through enhanced angiogenesis [80, 81] and myofibroblast-mediated wound contracture [81]. It is thought that the angiogenesis is in part the result of substance P-induced production and migration of endothelial cell progenitor cells from the bone marrow into injured peripheral tissue [82], as well as dermal microvascular endothelial cell proliferation [83].…”
Section: Substance Pmentioning
confidence: 99%